PENGARUH LAMA THAWING DALAM AIR ES (3°C) TERHADAP PERSENTASE HIDUP DAN MOTILITAS SPERMATOZOA SAPI BALI (Bos sondaicus) - Achmad Jaelani; M. Irwan Zakir; abdul Azis (LPPM Universitas Pekalongan, 2014)
The aim of this study was to find out effect of thawing lenght in ice water (3oC) to viability and motility of Bali’s cattle spermatozoa’s. This research was conducted in Februari 2014 at Balai Inseminasi Buatan Laboratory in Banjarbaru Kalimantan Selatan. The treatment was thawing lenght at 30,60,90 and 120 minutes. Each treatment needed 3 dose straw and 3 replication. Live percentage (%) and motility were perceived from the study. Data analysis used DMRT test. The result showed thawing lenghtwere significantly effect on viability and not significant on motility of Bali cattle spermatozoa . Keywords : thawing lenght, viability and motility